Revealing the Relationship Between Vocabulary Mastery and Listening Skills - Bradhiansyah Tri Suryanto (Universitas Nurul Jadid, 2023)
The relationship between vocabulary mastery and English listening skills at a given level—in this case, at the basic level—is examined in further detail, it will become more exciting and remarkable. This study attempts to demonstrate the connection between vocabulary knowledge and English listening skills in order to comprehend the relationship between the two on a basic level. This study used a correlational research methodology. This research technique looked at the relationship between vocabulary mastery and students' basic listening skills in English. The summary of the research findings above makes it evident that there is a weak but favourable correlation between basic vocabulary mastery and basic level listening skills. 0.0339 is the correlation coefficient. This suggests that other factors have a greater impact than basic vocabulary proficiency, which only has a 3.39% effect on the worth of basic listening skills. Based on the results of the ANOVA study, it is then found that the significance value of F is higher than the alpha value. As a result, there is less of a connection between basic vocabulary knowledge and basic listening skills. Additionally, by rejecting H0 and accepting H1, this study establishes a nonlinear regression line for the relationship between variables X and Y.